Efficacy and tolerability of adjunctive perampanel treatment in children under 12 years of age with refractory epilepsy - Yuni Yun; Dongsub Kim; Yun-Jeong Lee; Soonhak Kwon; Su-Kyeong Hwang (Korean Pediatric Society, 2019)
Purpose There is limited data on the use of perampanel in children under 12 years of age. We evaluated the efficacy and tolerability of adjunctive perampanel treatment in children under 12 years of age with refractory epilepsy. Methods This retrospective observational study was performed in Kyungpook National University Hospital from July 2016 to March 2018. A responder was defined as a patient with ≥50% reduction in monthly seizure frequency compared with the baseline. Adverse events and discontinuation data were obtained to evaluate tolerability. Results Twenty-two patients (8 males, 14 females) aged 3.1-11.4 years (mean, 8.0±2.5 years) were included in this study. After an average of 9.2 months (range, 0.5-19 months) of follow-up, 15 patients (68%) showed a reduction in seizure frequency, including 5 patients (23%) with seizure freedom. The age at epilepsy onset was significantly lower (P=0.048), and the duration of epilepsy was significantly longer (P=0.019) in responders than in nonresponders. Nine patients (41%) experienced adverse events, including somnolence (23%), respiratory depression (9%), violence (4.5%), and seizure aggravation (4.5%). The most serious adverse event was respiratory depression, which required mechanical ventilation in 2 patients (9%). Eight patients (36%) discontinued perampanel due to lack of efficacy or adverse events. Three out of 4 patients (75%) who discontinued perampanel due to adverse events had an underlying medical condition. Conclusion Perampanel offers a treatment option for refractory epilepsy in children. Adjunctive treatment with perampanel requires special consideration in those with underlying medical conditions to prevent serious adverse events.